"I need to know what makes somebody tick …": Challenges and Strategies of Implementing Shared Decision‐Making in Individualized Oncology. (6th September 2018) - Haltaufderheide, Joschka; Wäscher, Sebastian; Bertlich, Bernhard; Vollmann, Jochen; Reinacher‐Schick, Anke; Schildmann, Jan
Abstract: Background: Shared decision‐making (SDM) has been advocated as an ethical framework for decision‐making in cancer care. According to SDM, patients make decisions in light of their values and based on the available evidence. However, SDM is difficult to implement in cancer care. A lack of applicability in practice is often reported. This empirical‐ethical study explores factors potentially relevant to current difficulties in translating the concept of SDM into clinical practice. Methods: This study was conducted with nonparticipant observation of the decision‐making process in patients with gastrointestinal cancers for whom the benefit of adjuvant chemotherapy was uncertain according to clinical guidelines. Triangulation of qualitative data analysis was conducted by means of semistructured interviews subsequent to the observation. Observation notes and interview transcripts were analyzed according to the principles of grounded theory. Results: Deviating from the concept of SDM, oncologists initiated a process of eliciting values and medical information prior to conveying information. The purpose of this approach was to select and individualize information relevant to the treatment decision. In doing so, the oncologists observed used two strategies: "biographical communication" and a "metacommunicative approach." Both strategies could be shown to be effective or to fail depending on patients' characteristics such as their view of the physicians' role and the relevance of value‐related information for medical decision‐making. Conclusion: In contrast to the conceptual account of SDM, oncologists are in need of patient‐related information prior to conveying information. Both strategies observed to elicit such information are in principle justifiable but need to be adapted in accordance with patient preferences and decision‐making styles. Implications for Practice: This study showed that knowledge of patients' values and preferences is very important to properly adapt the giving of medical information and to further the process of shared decision‐making. Shared decision‐making (SDM) trainings should consider different strategies of talking about values. The right strategy depends largely on the patient's preferences in communication. To be aware of the role of values in SDM and to be able to switch communicative strategies might prove to be of particular value. A more systematic evaluation of the patient's decision‐making preferences as part of routine procedures in hospitals might help to reduce value‐related barriers in communication. Abstract : Although shared decision making is advocated in most fields of medicine, implementation in oncology is challenging. Considering the importance of patient involvement in the era of individualized oncology, this article analyzes barriers to shared decision making.